Roles of the Retinotopic and Environmental Frames of Reference on Vection - Fujimoto, Kanon; Ashida, Hiroshi (Frontiers in Virtual Reality, 2020)
Humans perceive self-motion using multisensory information, while vision has a dominant role as is utilized in virtual reality technologies. Previous studies reported that visual motion presented in the lower visual field (LoVF) induces stronger illusion of self-motion (vection) as compared with the upper visual field (UVF). However, it was still unknown whether the LoVF superiority in vection was based on the retinotopic frame, or rather related to the environmental frame of reference. Here, we investigated the influences of retinotopic and environmental frames on the LoVF superiority of vection. We presented a planer surface along the depth axis in one of four visual fields (upper, lower, right or left). The texture on the surface moved forward or backward. Participants reported vection while observing the visual stimulus through a VR HMD in the sitting posture or lateral recumbent position. Results showed that the visual motion induced stronger vection when presented in the LoVF compared with the UVF in both postures. Notably, the vection rating in LoVF was stronger in the sitting than in the recumbent. Moreover, recumbent participants reported stronger vection when the stimulus was presented in the gravitationally lower field than in the gravitationally upper field. These results demonstrate contribution of multiple spatial frames on self-motion perception and imply the importance of ground surface.